Development of the Is-Me Board Game to Instill Religious Values and Love for Malay Culture in Children Aged 4-6 Years - Lina Eka Retnaningsih; Mahfuzah Saniah; Hany Faizah (JOYCED: Journal of Early Childhood Education, 2024)
Early childhood is referred to as the golden age, which is in the foundational phase. In this era, the prevalence of online games that children can play for long periods has many negative impacts on their development. Currently, there is a lack of educational play tools that encourage children to engage in activities, develop Islamic values, and foster a love for Malay culture. The purpose of this research is to develop the Is-Me board game with themes of Islam and Malay culture so that it can be used to instill religious values and a love for Malay culture in children aged 4-6 years. This study uses a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, and Dissemination). The validity level from material experts reached 90%, while media experts reached 91%. The research results show that the Is-Me board game media developed using the 4D model can be considered feasible for use, as confirmed by the validity test involving material and media experts, and it has been trialed for the use of the media.